2014
DOI: 10.1021/ac503697j
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flanking Sequences for Peptides Included in a Quantification Concatamer Internal Standard

Abstract: Quantification by targeted proteomics has largely depended on mass spectrometry and isotope-labeled internal standards. In addition to traditionally used recombinant proteins or synthetic peptides, concatenated peptides (QconCATs) were introduced as a conceptually new source of internal standard. In the present study, we focused on assessing the length of natural flanking sequences, which surround each peptide included in QconCAT and provide for identical rates of analyte and standard digestion by trypsin. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Thus, digestion efficiency of the concatenated surrogate peptides in a conventional QconCAT protein can differ significantly from that of the peptides in native proteins, which imposes significant challenges on the accuracy and repeatability of QconCAT-based quantitative proteomics. Cheung et al assessed the effect of natural amino acid flanking sequence on trypsin digestion efficiency of QconCAT proteins and concluded that including six or more amino acid flanking residues is necessary for reliable quantification 30 . In the preset study, we included at least 15 native flanking amino acids to ensure accurate measurement of any departure of ASPE ratios from one.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, digestion efficiency of the concatenated surrogate peptides in a conventional QconCAT protein can differ significantly from that of the peptides in native proteins, which imposes significant challenges on the accuracy and repeatability of QconCAT-based quantitative proteomics. Cheung et al assessed the effect of natural amino acid flanking sequence on trypsin digestion efficiency of QconCAT proteins and concluded that including six or more amino acid flanking residues is necessary for reliable quantification 30 . In the preset study, we included at least 15 native flanking amino acids to ensure accurate measurement of any departure of ASPE ratios from one.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not evaluated digestion efficiency directly, these results indirectly support similar digestion efficiencies between the target and standard proteins and between the tertiary PCSs and HSA, regardless of background proteins, and thereby the reliability of the quantification presented here. In the meanwhile, as amino acid residues surrounding the cleavage sites of more than three have been reported to have potential effect on missed cleavage , longer flanking sequences (e.g., six residues) might be required for more identical digestion efficiencies of the target and standard proteins. The stability and degradation of peptides can also provide a bias for absolute measurement.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,18,19 The amino acid sequences of EXO1 and EXO2 QconCATs designed for quantification of EVs proteins are shown in Figure S1 (Supporting Information). The synthetic genes encoding these sequences were synthesized and incorporated into the pET21a expression vector, with codon optimization for E. coli (Biomatik, Cambridge, Ontario).…”
Section: Methodsmentioning
confidence: 99%